2014
DOI: 10.1016/j.athoracsur.2014.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Initial Diagnostic Strategies for Pulmonary Nodules Presenting to Thoracic Surgeons

Abstract: Background Patients presenting to thoracic surgeons with pulmonary nodules suspicious for lung cancer have varied diagnostic options including navigation bronchoscopy (NB), computed tomography fine needle aspiration (CT-FNA), 18F-fluoro-deoxyglucose positron emission tomography (FDG-PET) and video assisted thoracic surgery (VATS). We studied the relative cost-effective initial diagnostic strategy for a 1.5-2 cm nodule suspicious for cancer. Methods A decision analysis model was developed to assess the costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 26 publications
0
61
0
Order By: Relevance
“…erefore, it is expected that 18 F-FDG PET/CT is reported in the list of approved procedures for the investigation of SPNs in several countries [24]. On the other hand, it is expected that 18 F-FDG PET/CT may not be cost-effective for early diagnosis of LC in regions or countries where the specificity of this method is low (i.e., in countries where infectious lung diseases are endemic) Contrast Media & Molecular Imaging [25]. In summary, in countries with a low incidence of pulmonary inflammatory or infectious diseases and a high incidence of LC, the diagnostic workup of SPNs should include 18 F-FDG PET/CT as a main pillar.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, it is expected that 18 F-FDG PET/CT is reported in the list of approved procedures for the investigation of SPNs in several countries [24]. On the other hand, it is expected that 18 F-FDG PET/CT may not be cost-effective for early diagnosis of LC in regions or countries where the specificity of this method is low (i.e., in countries where infectious lung diseases are endemic) Contrast Media & Molecular Imaging [25]. In summary, in countries with a low incidence of pulmonary inflammatory or infectious diseases and a high incidence of LC, the diagnostic workup of SPNs should include 18 F-FDG PET/CT as a main pillar.…”
Section: Discussionmentioning
confidence: 99%
“…However, our work has questioned the use of FDG-PET/CT for the diagnosis of suspicious IPNs where fungal lung diseases are endemic. 6,8,20,21 Limitations of this study include our reliance on data from areas, with endemic fungal infections as well as the lack of prospective data collection with multiple cohorts specifically designed to represent a range of cancer prevalence, exposure to fungal lung disease, and other variables. Positron emission tomography specificity was highest in the Massachusetts cohort, a population with minimal fungal lung diseases and whose measured endemic rate is far lower than that of the other states’ cohorts (1.1%).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In a cost-effectiveness study comparing diagnostic FDG-PET/CT scan with aggressive tissue acquisition, we have previously reported that clinicians should pursue diagnosis by pathological tissue procedures instead of a diagnostic FDG-PET/CT scan when the specificity of FDG-PET/CT is less than 72%. 21 Frequent use of preoperative tissue acquisition strategies has been shown to result in lower rates of nontherapeutic lung resections. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The cutoff points are based on cost-effectiveness studies and clinical guidelines for the management of IPNs. 6,22 …”
Section: Discussionmentioning
confidence: 99%